ANALISIS FAKTOR-FAKTOR LINGKUNGAN HUTAN MANGROVE PANTAI PASURUAN - Chatarina Muryani, (Pendidikan Geografi, 2010)
<!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.PreformattedText, li.PreformattedText, div.PreformattedText mso-style-name:"Preformatted Text"; mso-style-unhide:no; margin:0cm; margin-bottom:.0001pt; mso-pagination:none; mso-hyphenate:none; font-size:10.0pt; font-family:"Courier New"; mso-fareast-font-family:"Courier New"; mso-fareast-language:#00FF; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page WordSection1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –> ABSTRACT : The aim of this research is  to know  the differences of environmental factors toward the thickness of mangrove forest. Samples chosen were the mangrove forest which had various thickness. Semare Village was chosen to represent west part of research area, Bugul Kidul District was chosen to represent middle part of research area, Penunggul Village and Kedawang Village at Nguling District were chosen to represent east part of the research area. For each thickness of mangrove forest, there were made 3 line transects from the mangrove forest land edge to the mangrove forest sea edge, upright the shore line. There were determined 3 plot samples to represent less thick mangrove forest, 6 plot samples to represent middle thick mangrove forest, and 9 plot samples to represent high thick mangrove forest.The results of this research showed that there were differences environment factors especially in organic matter of water and soils, soil texture, on the thickness mangrove forest.  Based on MANOVA analysis (simultaneous) there were differences on the environment factors on the thickness of mangrove forest.             Key words : mangrove forest , environment factors <!– /* Font Definitions */ @font-face font-family:Wingdings; panose-1:5 0 0 0 0 0 0 0 0 0; mso-font-charset:2; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:0 268435456 0 0 -2147483648 0; @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page WordSection1 size:21.0cm 842.0pt; margin:3.0cm 3.0cm 3.0cm 3.0cm; mso-header-margin:42.55pt; mso-footer-margin:2.0cm; mso-columns:2 even 17.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; @page WordSection2 size:21.0cm 842.0pt; margin:3.0cm 3.0cm 3.0cm 3.0cm; mso-header-margin:42.55pt; mso-footer-margin:2.0cm; mso-paper-source:0; div.WordSection2 page:WordSection2; @page WordSection3 size:21.0cm 842.0pt; margin:3.0cm 3.0cm 3.0cm 3.0cm; mso-header-margin:42.55pt; mso-footer-margin:2.0cm; mso-columns:2 even 17.0pt; mso-paper-source:0; div.WordSection3 page:WordSection3; @page WordSection4 size:21.0cm 842.0pt; margin:3.0cm 3.0cm 3.0cm 3.0cm; mso-header-margin:42.55pt; mso-footer-margin:2.0cm; mso-paper-source:0; div.WordSection4 page:WordSection4; @page WordSection5 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection5 page:WordSection5; /* List Definitions */ @list l0 mso-list-id:370768600; mso-list-type:hybrid; mso-list-template-ids:423937736 67698689 1982736072 67698693 67698689 67698691 67698693 67698689 67698691 67698693; @list l0:level1 mso-level-number-format:bullet; mso-level-text:; mso-level-tab-stop:36.0pt; mso-level-number-position:left; text-indent:-18.0pt; font-family:Symbol; @list l0:level2 mso-level-start-at:0; mso-level-number-format:bullet; mso-level-text:-; mso-level-tab-stop:72.0pt; mso-level-number-position:left; text-indent:-18.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:"Times New Roman"; @list l1 mso-list-id:826479956; mso-list-type:hybrid; mso-list-template-ids:1336729930 2076329866 -1730516508 -1858180590 67698703 67698713 67698715 67698703 67698713 67698715; @list l1:level1 mso-level-text:"(%1)"; mso-level-tab-stop:36.75pt; mso-level-number-position:left; margin-left:36.75pt; text-indent:-18.75pt; @list l1:level2 mso-level-start-at:0; mso-level-number-format:bullet; mso-level-text:-; mso-level-tab-stop:72.0pt; mso-level-number-position:left; text-indent:-18.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:"Times New Roman"; @list l1:level3 mso-level-tab-stop:117.0pt; mso-level-number-position:left; margin-left:117.0pt; text-indent:-18.0pt; @list l2 mso-list-id:880358418; mso-list-type:hybrid; mso-list-template-ids:426784594 -488846648 67698689 67698693 67698689 67698691 67698693 67698689 67698691 67698693; @list l2:level1 mso-level-number-format:bullet; mso-level-text:-; mso-level-tab-stop:90.0pt; mso-level-number-position:left; margin-left:90.0pt; text-indent:-18.0pt; @list l2:level2 mso-level-number-format:bullet; mso-level-text:; mso-level-tab-stop:107.85pt; mso-level-number-position:left; margin-left:107.85pt; text-indent:-18.0pt; font-family:Symbol; @list l3 mso-list-id:1655602515; mso-list-type:hybrid; mso-list-template-ids:1581806676 67698699 447510896 853018220 67698703 67698713 67698689 635761154 67698713 67698715; @list l3:level1 mso-level-number-format:bullet; mso-level-text:; mso-level-tab-stop:36.0pt; mso-level-number-position:left; text-indent:-18.0pt; font-family:Wingdings; @list l3:level2 mso-level-tab-stop:72.0pt; mso-level-number-position:left; text-indent:-18.0pt; @list l3:level3 mso-level-number-format:alpha-lower; mso-level-tab-stop:117.0pt; mso-level-number-position:left; margin-left:117.0pt; text-indent:-18.0pt; @list l3:level4 mso-level-tab-stop:144.0pt; mso-level-number-position:left; text-indent:-18.0pt; @list l3:level5 mso-level-number-format:alpha-lower; mso-level-tab-stop:180.0pt; mso-level-number-position:left; text-indent:-18.0pt; @list l3:level6 mso-level-number-format:bullet; mso-level-text:; mso-level-tab-stop:225.0pt; mso-level-number-position:left; margin-left:225.0pt; text-indent:-18.0pt; font-family:Symbol; @list l3:level7 mso-level-number-format:alpha-lower; mso-level-text:"(%7)"; mso-level-tab-stop:252.0pt; mso-level-number-position:left; text-indent:-18.0pt; @list l4 mso-list-id:2098671390; mso-list-type:hybrid; mso-list-template-ids:-2055587152 67698713 67698713 67698715 67698703 67698713 67698715 67698703 67698713 67698715; @list l4:level1 mso-level-number-format:alpha-lower; mso-level-tab-stop:36.0pt; mso-level-number-position:left; text-indent:-18.0pt; ol margin-bottom:0cm; ul margin-bottom:0cm; –